Analyzing the Phenomenon of Divorce from the Perspective of Expert Family Therapists: A Grounded Theory Sample - Hojaji, Maraym; Naghsh , Zahra; Salehi, Keyvan; Afrooz, Gholamali (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study was conducted with the aim of analyzing the phenomenon of divorce from the perspective of expert family therapists. Method: The research method was qualitative, based on grounded theory (Charmaz, 2014). The research setting included all family therapists in the city of Isfahan in the year 2024, and the participants consisted of ten of the most prominent therapists who were purposefully selected. The research tool was interviews conducted in the form of focus groups. The collected data were analyzed using Charmaz’s (2014) method: first, coding was carried out, followed by conceptualization. Then, during the process of integration, categories were extracted, and finally, the core categories were identified and the theory was formed. Results: The results indicated that the phenomenon of divorce includes three main categories: (1) the reasons behind the occurrence of divorce: the activators of divorce causes, with categories such as changes in cultural and social structures and the prioritization of individuality over couplehood; (2) the nature of divorce causes: causes of divorce categorized as changes in family roles and authority, poor spouse selection, inappropriate communication, and individual problems; and (3) the process through which the causes interconnect: integrators of divorce causes (disturbance-power, disturbance-intimacy, and boundary disturbances). Conclusion: Based on the findings, this study suggests that in order to reduce divorce, the activators of divorce cannot be ignored, as they render society more prone to facilitating the grounds for divorce rather than preserving family stability. Additionally, the identified causes of divorce indicate that many revolve around the philosophy of individualism. Therefore, society and societal discourse must reinforce the value of collectivism so that this value can function as a socio-psychological superstructure acting as a barrier to divorce.